Prognostic indices of clinical nursing practice in intensive care: an integrative review - Lucilane Maria Sales da Silva; Laércia Ferreira Martins; Cecília Cesarino Santos; Roberta Meneses Oliveira (Universidade Federal de Goias, 2014)
The objective of this integrative review was to analyze the scientific production in nursing on prognostic indices in clinical practice in intensive care. A search of Medline (Retrieval System Online and Medical Literature Analysis), PubMed (National Library of Medicine) and Scopus (Elsevier) resulted in 12 articles, which were analyzed considering the following thematic categories: Prognostic indices for severity assessment in critical patients; and Prognostic indices as guiding instruments of clinical practice and nursing care management in the ICU. It was inferred that using prognostic indices in clinical practice and in care management remains incipient, but is growing in nursing. Nevertheless, there is a greater utilization of indices particular of nursing (TISS-28; NAS). The latter are a starting point to quantify and qualify the delivered care, and are useful tools for material human resource management, as they allow for incorporating scientific-technological evidence that are required for delivering care to critical patients. Descriptors: Nursing; Severity of Illness Index; Nursing Care; Intensive Care; Prognosis.